Application of Theory of Planned Behavior on Factors Associated with Pap Smear Uptake: A Meta-Analysis - Elvira Purnamasari; Argyo Demartoto; Uki Retno Budihastuti (Journal of Health Promotion and Behavior, 2024)
Background: Pap smear is a cervical cancer prevention method that has been proven to be effective in reducing the incidence of cervical cancer. Utilization of Pap smears is influenced by various factors. Family or partner support can also affect the use of Pap smears in women of reproductive age. This study aimed to estimate the effects of Theory of Planned Behavior (TPB) and family support on Pap Smear utilization. Subjects and Method: This was a systematic review and meta-analysis based on data obtained through Google Scholar, PubMed, and Science Direct published in the last 10 years. Article search was performed using the PICO model. Population: women of reproductive age. Intervention: positive attitude, perception of strong behavioral control and positive family support. Comparison: negative attitude, perception of weak behavioral control and negative family support. Outcome: utilization of Pap smears. Article searches were carried out using the keywords “Papanicolau test” OR “Pap test” AND “attitude” AND “self-efficacy” OR “perceived behavior control” AND “family support” OR “spouse support” OR “husband support”. The article used is full text in English with a cross sectional design. Articles were collected using PRISMA flow diagrams and then analyzed using the Review Manager 5.4 application. Results: 22 cross-sectional study from Nigeria, Ghana, South Africa, Uganda, Ethiopia, Malaysia, Hong Kong, Iran, and the US were selected for meta-analysis. The total sample size is 13,330. Recent meta-analysis found that positive attitude (aOR= 1.53; 95% CI= 1.35 to 1.72; p<0.001) and perceived strong behavioral control (aOR= 2.01; 95% CI= 1.56 to 2.59; p< 0.001) increased Pap smear utilization. Strong family support increased Pap smear utilization, but it was statistically non-significant (aOR= 2.53; 95% CI= 0.79 to 8.10; p< 0.001). Conclusion: Positive attitudes, perceptions of strong behavioral control and positive family support can increase Pap smear utilization.